2017
DOI: 10.1111/apha.13006
|View full text |Cite
|
Sign up to set email alerts
|

The interstitium conducts extrarenal storage of sodium and represents a third compartment essential for extracellular volume and blood pressure homeostasis

Abstract: The role of salt in the pathogenesis of arterial hypertension is not well understood. According to the current understanding, the central mechanism for blood pressure (BP) regulation relies on classical studies linking BP and Na balance, placing the kidney at the very centre of long-term BP regulation. To maintain BP homeostasis, the effective circulating fluid volume and thereby body Na content has to be maintained within very narrow limits. From recent work in humans and rats, the notion has emerged that Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 131 publications
(346 reference statements)
1
69
0
2
Order By: Relevance
“…This suggested a missing mechanism for removal of sodium from the circulation. Recent studies have brought to light the role of nonosmotic peripheral sodium storage in regulating sodium balance . Thus, we updated the model with a peripheral nonosmotic sodium storage compartment.…”
Section: Case Study 1: Cardio‐renal Drug‐disease Qsp Modeling Enabledmentioning
confidence: 99%
“…This suggested a missing mechanism for removal of sodium from the circulation. Recent studies have brought to light the role of nonosmotic peripheral sodium storage in regulating sodium balance . Thus, we updated the model with a peripheral nonosmotic sodium storage compartment.…”
Section: Case Study 1: Cardio‐renal Drug‐disease Qsp Modeling Enabledmentioning
confidence: 99%
“…Although this model is grossly oversimplified [6,7], it is still useful for clinical purposes. These body compartments can be estimated using tracer dilution methods, although this is impractical in a clinical setting.…”
Section: Fluid Volume Compartmentsmentioning
confidence: 99%
“…Building upon older observations, Titze et al [7] designed a new paradigm in which the skin attained a novel role in blood pressure regulation by nonosmotic sodium storage. Recently, Olde Engberink et al [14] observed that after infusion of hypertonic saline in healthy volunteers, only 47% could be retrieved in the urine, suggesting substantial sodium buffering.…”
Section: Non-osmotic Sodium Storagementioning
confidence: 99%
See 2 more Smart Citations